Analysis of Nasal Septal Deviation Types on Sinusitis Incidence: Literature Review - Ristyana, Sabira Husna; Povitasari, Povitasari; Andarista, Aprilia Intan; Adji, Iwan Setiawan (Newinera Publisher, 2025)
Nasal septal deviation is a common anatomical abnormality found in the general population and is thought to play a role in the pathogenesis of sinusitis. Some types of nasal septal deviation can impair sinus drainage and airflow, leading to inflammation and infection. However, there is no consensus on which type of septal deviation contributes most to sinusitis. Objective: This literature review aims to analyze and identify the types of nasal septal deviation that are most frequently associated with sinusitis. Methods: The data review was conducted using the PRISMA method, with data searches from PubMed, Google Scholar, ScienceDirect and Wiley with research data criteria between 2020-2024. The keywords used to search for data were